New Insights into Development of an Environmental – Economic Model Based on a Composite Environmental Quality Index: A Comparative Analysis of Economic Growth and Environmental Quality Trend - Hossein-Ali Fakher; Mostafa Panahi; Karim Emami; Kambiz Peykarjou; Seyed Yaghoub Zeraatkish (Environmental Energy and Economic Research)
In order to fill the research gap regarding the use of a comprehensive index that includes all dimensions of environmental pollution, this study sought to develop a composite environmental quality index to tackle with the possible bias and remove the possible linearity in the experimental research model. Principal Component Analysis (PCA) and Artificial Neural Network (ANN) methods were used to obtain this composite index. This study used six environmental indicators from two groups of Organization of Petroleum Exporting Countries (OPEC) and Organization for Economic Co-operation and Development (OECD) during 2008-2019. According to the obtained error criteria related to the two methods, ANN method was used to calculate the weight of environmental indicators due to having the lowest error criteria and therefore reliable results. Finally, using this composite index, the trend of economic growth and environmental quality were analyzed graphically. The results showed that along with the upward trend of economic growth, the quality of environment follows a downward trend in OPEC countries and an upward trend in OECD countries. At the end of this paper, some limitations of study are presented, and some suggestions for future studies are provided as well.